The study of consumers' perception towards cashless transaction mode in Islamic Banking among students in Malaysia - Nur Rabiatul Adawiyah Aris; Nur Rasyidah Abd Rashid; Nur Sabrina Mohd Najmi; Nur Salsabilla Syahira Ramli (2024)
In today's era of globalization, cashless payment has become one of the choices of many people today, regardless of whether they are already working or students. This is said to be so because the use of cashless payments is more comfortable and safer to use in all daily affairs and business. Not only the students, but all the community agrees that this cashless payment provides many conveniences such as easy tracking of any expenses and transactions including saving time. This research aims to study the consumers' perception towards cashless transaction mode in Islamic banking among students in Malaysia. The objective of this research is to examine the relationship between privacy and security, social influence, convenience, acceptance, and consumers’ perception towards cashless transactions in Islamic banking among students in Malaysia. There are 384 respondents gathered in total. Quantitative research is used in this study. Data was analyzed using SPSS methods, including a reliability test, descriptive analysis, and Spearman’s Correlation Analysis. The findings of this study explain that there is a positive and significant relationship between privacy and security, social influence, convenience, acceptance, and consumers’ perception towards cashless transactions in Islamic banking among students in Malaysia. The findings from this study are logical to be involved in future research.